NOTARY LEGALITY AS AN AUTHENTIC DICTION IN TERMS OF PHYSICALLY DISABLED BASED ON LAW OF POSITION NOTARY - Ida Ayu Ratna Kumala; Ni Luh Made Mahendrawati; I Nyoman Alit Puspadma (NOTARIIL Jurnal Kenotariatan, 2021)
An authentic deed can be perfect proof that must be signed by the parties. It becomes a problem when one or all of those who are obliged to sign or put fingerprints, but have a total disability of the hand or fingers (physically disabled) so that the person concerned is not able to sign or fingerprint. There is a norm in relation to a person with disabilities to make a deed before a notary. The purpose of this study is to find out the procedure for ratifying a notary deed in terms of hearing-impaired persons and the legal strength of a notary deed in terms of disabled persons. This study uses normative legal methods. The results of this study indicated that the stipulation of Article 44 of UUJNP makes it possible for persons with disabilities not to sign the deed, then at the end of the deed it is explained about a situation where the applicant is unable to sign the deed and therefore uses other forms of endorsement by writing by mouth and affidavit. The deed made by the person with disabilities is an authentic deed because the provisions of Article 44 UUJNP can be a substitute for signatures, so the notary deed made by persons with disabilities can function as evidence and are equipped with an affidavit. There is a need for a written rule that states clearly about the procedures for dealing with persons with disabilities in making a deed for the use of affidavit.